CdS/Bi12O17Cl2 Heterostructure Promotes Visible-Light-Driven Photocatalytic CH4 Generation and Phenol Conversion - Dandan Hu; Yumin Cui; Xiaoyan Cao; Yan Han; Huiquan Li; Hui Miao; Yuying Wu; Huidan Yang; Wei Zhao; Chaonan Xu; Yupeng Yuan (International Journal of Photoenergy)
We report a heterojunction photocatalyst by coupling CdS with Bi12O17Cl2 via a facile thermal annealing process. Such heterostructure can promote the charge separation between CdS and Bi12O17Cl2, thereby leading to a considerable improvement on the performance for CO2 reduction into valuable CH4 and phenol conversion under visible light exposure. The CdS/Bi12O17Cl2 heterojunction with mass ratio of 1 : 1 (50% CdS/Bi12O17Cl2) shows the highest CH4 production rate (1.28 μmol·h-1·g-1), which is as 9.8 and 5.8 times as the CH4 generation rate of pure Bi12O17Cl2 and CdS (0.13 and 0.22 μmol·h-1·g-1), respectively. Also, the 50% CdS/Bi12O17Cl2 sample shows the highest activity of phenol conversion with a conversion ratio of 92%, which is as 2.2 times and 1.9 times as the conversion ratio of pristine Bi12O17Cl2 (41%) and CdS (48%), respectively. The present study demonstrates the great potential of the CdS/Bi12O17Cl2 heterojunction for efficient charge separation towards increased photocatalytic CH4 production and phenol conversion.